Anamnesis: a memória de um não-lugar - Marcolino, Amanda Cristina [UNESP] (Universidade Estadual Paulista (Unesp), 2017)
The word Anmnesis refers to a quest of a collective memory that is intrinsic at human relations. The purpose of the project is to obtain visual data that could portrays the community search for identity from one of the largest urban scars from São Paulo's city, the Minhocão. Besides, the project aims to improve the discussion about the points that are in schedule about public space appropriation and the re-adaptation of the urban project. Over a collection of local photographs and montages that relates the temporal events in a space of scarce identity, the final result of the project shows itself as an essay of the passage of time as the memory of a non-place.

O termo Anmnesis faz menção a uma busca de uma memória coletiva que está intrínseca nas relações humanas. O intuito do projeto é a obtenção de dados visuais que possam retratar a busca da comunidade pela identidade de uma das maiores cicatrizes urbanas da cidade de São Paulo, o Minhocão; além de levantar os questionamentos que estão em pauta acerca da apropriação do espaço público e da readequação do projeto urbano. A partir de fotografias do local e de montagens que relacionam os acontecimentos temporais em um espaço de escassa identidade, o resultado final se mostra como um ensaio da passagem do tempo como a memória de um nãolugar.
Keywords: Memória; Anamnese; Tempo; Fotografias; Photography